Analyzing the Critical Thinking Skills of 5th Grade Students on the Respiratory System Material Using a Qualitative Descriptive Method - Purnamasari, Asri Indah; Prahani, Binar Kurnia; Suryanti (Universitas Veteran Bangun Nusantara, 2025)
Critical thinking skills are crucial for preparing students to face complex real-world problems and are a key component of 21st-century learning. This study aims to identify the critical thinking skill profile of 5th-grade elementary school students on the respiratory system material. Critical thinking is an essential skill in 21st-century education, particularly for developing students' abilities in analysis, evaluation, and argumentation. However, it is often neglected in science education at the elementary level. This research employs a qualitative descriptive method with survey techniques. Data were collected through questionnaires, interviews, and classroom observations to assess students' critical thinking skills. The results indicate that among the 30 students tested, 15 were categorized as Fair, 12 as Low, and only 3 as Good. No student achieved the Very Good or Very Low category. The analysis of critical thinking indicators including analyzing, evaluating, composing arguments, and problem-solving reveals that while students possess a basic understanding, they struggle with more advanced critical thinking tasks. The study concludes that students' critical thinking skills remain limited to basic comprehension. This limitation is attributed to the dominance of rote learning methods and the lack of interactive and problem-solving-based instructional strategies. Future teaching approaches should prioritize active learning and the integration of critical thinking practices to enhance students' higher-order thinking skills.